REVEALING TAX AVOIDANCE IN THE FAMILY-OWNED COMPANY: ETHNOMETHODOLOGY STUDY - Maron, Wempi; Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2016)
This paper dismantles the occurance of Tax Avoidance found in the family company in Malang. The method used in this research is etnomethodology, a method that is used to investigate indexical expressions and other practical actions as a unified settlement that is being done (the organized Tax Avoidance) and how to apprehed their everyday world. It is mentioned in the beginning that there are a number of factors which cause tax avoidance, that is a drive to "enrich" themselves faster, gluttony, stingy, and a number of lust rage. It is also revealed that the practice of trailing attitude is driven by a fact that there are companies which do not pay taxes but they are safe. The presence of the National Land Agency (Badan Pertanahan Nasional), local governments and tax officials who must be "serviced", in fact also trigger the occurrence of tax avoidance. These kind of activities were uncovered due to the fictitious reports. There were no data and report books, the bank account is mixed between the personal and company affairs. They create their own cheating reports which are set up by themselves. They even wish that the tax officials do not need to check the tax affairs in the company if it is possible. Thus, the data reported are all fictitious and the bank flux does not appear. They are all manipulative reports. The impacts of this situation are very much felt by the employees, such as the emergence of envy, suspicion among them, being tensed when they have to manipulate data, blaming on each other, and throwing out reponsibilities to each other. Psychologically, the impact to employees leads to being depressed and stressed due to the unclear payroll, resentmented, and hurt because of unfair treatments. Lastly, it is revealed that the solution to some of these problems are by apologizing and doing permissive attitude, such as â€œwe apologize for any error, please help us, thank you profuselyâ€, and any kinds of apologies which will get prevalent from others. Those attitudes are also followed by permissive attitudes, for instance stating that â€œwhat we are doing is an emergency, and that the condition is very much stangling making the company havino other better choice, so please understandâ€. As a practical implication, this Tax Avoidance practices can bring collusion, nepotism, and even corruptions to various stakeholders, such as National Land Agency (Badan Pertanahan Nasional), the local government, tax officers and tax consultants due to the susceptible of informal negotiation.